PROGNOSIS OF INHALATION INJURY MORTALITY RATE WITH REVISED BAUX SCORE AT DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA (2019-2021) - Dhea Hasna Salsabilla; Agus Santoso Budi; Diah Mira Indramaya; Ronaldo Muslim (Jurnal Rekonstruksi dan Estetik)
Highlights: